Respuesta :

gmany
First brackets:
(9 : 3) = 3(6 - 7) = (-1)
Next product
4(6 - 7) = 4(-1) = -4
Next sum
(9 : 3) + 4(6 - 7) = 3 + (-4) = -1
Answer: b) -1

Answer:

b) [tex]-1[/tex].

Step-by-step explanation:

We are asked to find the value of the expression [tex](\frac{9}{3})+4(6-7)[/tex].

We will use order of operations (PEMDAS) to solve our given problem.

P: Parenthesis,

E : Exponent,

M/D : Multiply/Divide (From left to right)

A/S : Add/Subtract (From left to right)

First of all, we will remove parenthesis as:

[tex]3+4(-1)[/tex]

[tex]3-4[/tex]

[tex]-1[/tex]

Therefore, the value of our given expression is [tex]-1[/tex].